Neo1 and phosphatidylethanolamine contribute to vacuole membrane fusion in Saccharomyces cerevisiae. Issue 3 (2nd July 2016) - Wu, Yuantai; Takar, Mehmet; Cuentas-Condori, Andrea A.; Graham, Todd R.
ABSTRACT: NEO1 is an essential gene in budding yeast and belongs to a highly conserved subfamily of P-type ATPase genes that encode phospholipid flippases. Inactivation of temperature sensitive neo1 ts alleles produces pleiomorphic defects in the secretory and endocytic pathways, including fragmented vacuoles. A screen for multicopy suppressors of neo1-2 ts growth defects yielded YPT7, which encodes a Rab7 homolog involved in SNARE-dependent vacuolar fusion. YPT7 suppressed the vacuole fragmentation phenotype of neo1-2, but did not suppress Golgi-associated protein trafficking defects. Neo1 localizes to Golgi and endosomal membranes and was only observed in the vacuole membrane, where Ypt7 localizes, in retromer mutants or when highly overexpressed in wild-type cells. Phosphatidylethanolamine (PE) has been implicated in Ypt7-dependent vacuolar membrane fusion in vitro and is a potential transport substrate of Neo1. Strains deficient in PE synthesis ( psd1Δ psd2Δ ) displayed fragmented vacuoles and the neo1-2 fragmented vacuole phenotype was also suppressed by overexpression of PSD2, encoding a phosphatidylserine decarboxylase that produces PE at endosomes. In contrast, neo1-2 was not suppressed by overexpression of VPS39, an effector of Ypt7 that forms a membrane contact site potentially involved in PE transfer between vacuoles and mitochondria. These results support the crucial role of PE in vacuole membrane fusion and implicate Neo1 in concentrating PE in the cytosolic leaflet of Golgi and endosomes, and ultimately the vacuole membrane.